2009
DOI: 10.1097/phh.0b013e3181a391e2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Public Health Department Employees' Willingness to Report to Work During an Influenza Pandemic

Abstract: Nearly half of public health department employees are unwilling to report to work during the peak of an influenza pandemic when the public health response will be a vital component of pandemic containment and mitigation. In light of the current worldwide spread of novel influenza A (H1N1), there is an urgent need to better inform public health workers about their roles in pandemic response and to ensure that personal safety is a top priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 12 publications
4
74
0
Order By: Relevance
“…13,19,20 This study supports those findings. We found that when given hypothetical situations in which colleagues were being placed in quarantine or were dying of the flu, significantly fewer respondents reported a willingness to work.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…13,19,20 This study supports those findings. We found that when given hypothetical situations in which colleagues were being placed in quarantine or were dying of the flu, significantly fewer respondents reported a willingness to work.…”
Section: Discussionsupporting
confidence: 95%
“…Many studies have found that concerns about the adequacy of PPE affect willingness to work, 5,8,11,12,16,19,20,23,[25][26][27][28] and we found this to be one of the most powerful influences as well. While respondents reported being more likely to work if given adequate PPE (gown, gloves, and N-95 mask; or gloves and N-95 mask), some reported that they wouldn't work even with full PPE.…”
Section: Discussionmentioning
confidence: 91%
“…2009 Basta 32 72.6% of respondents considered family health and safety to be their greatest concern during an influenza pandemic. 92.3% of respondents were willing to work in the lowest risk scenario as compared with 56.2% in the highest risk scenario.…”
Section: Resultsmentioning
confidence: 98%
“…32 Past Experience with an Influenza Emergency-Tam et al reported that nurses who had previously worked during an influenza public health emergency were less likely to avoid influenza patients and to change their jobs. 23 Tzeng also found that nurses in the post-SARS group were more willing to provide care for patients with SARS than were those in the during-SARS group.…”
Section: Data Synthesismentioning
confidence: 97%
“…Fifteen studies -Basta et al [ [43], and Tippett et al [44] -examined willingness to report to work exclusively in an influenza pandemic but scenarios varied dramatically from study to study. For example, Basta et al [31] examined both early and peak pandemic duties to assess willingness to report to work contingent on duties requiring direct face to face contact with infected patients. Peak pandemic with high risk duties of direct face-to-face contacted produced a substantially lower willingness to report to work of 56.2%.…”
Section: Influenza Pandemic Eventsmentioning
confidence: 99%